PENERAPAN MODEL COOPERATIVE LEARNING TIPE TIME TOKEN UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWAnPADA TEMA DAERAH TEMPAT TINGGALKU DI KELAS IV SD NEGERI 101893BANGUN REJO KECAMATAN TANJUNG MORAWA - Rahmi Amelia Amar; Dinda Yarshal (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to increase students' self-confidence by applying a cooperative learning model of the time token type on the theme of the area where I live. This research was conducted in the fourth grade of SD Negeri 101893 Bangun Rejo, Tanjung Morawa. This research is a classroom action research (Classroom Action Research). The subjects in this study were fourth grade students, totaling 24 people, 11 male students and 13 female students. The instruments and data collection techniques used in this study were observation and documentation. From the results of observations, it is known that the overall teacher activity in the first cycle with the application of the time token type cooperative learning model is 56% or is in the sufficient category. In the second cycle is 69% or is in the good category. In the third cycle is 86% or is in the very good category. The overall activity of students using the time token type of cooperative learning model in the first cycle was 50%. In the second cycle is 66% with good category. In the third cycle is 83% with a very good category. Students' self-confidence in the first cycle is 56% classified as